The Analysis of Students’ Perceptions in Hybrid Classroom using Learning Management System (LMS) - Ari Susanto, Ahmad; -, ibrahim (Lingual Journal of Language and Culture, 2023)
This qualitative descriptive case study delves into the perceptions of students regarding the utilization of a Learning Management System (LMS) in a hybrid classroom setting and elucidates the challenges encountered by students while using the LMS. The research involved five junior high school students selected based on specific criteria and characteristics. Employing observation and interviews as the primary instruments, the study unfolded in distinct stages. The findings revealed varying perceptions among the students, with three displaying a positive outlook toward the use of LMS in hybrid classes, while the remaining two exhibited a negative perception. Challenges identified encompassed a lack of enthusiasm in engaging with both online and offline learning through the LMS, intermittent connectivity issues, tight deadlines, and difficulties in comprehending the instructional content delivered via the LMS.